Investigating a narrative based approach to leader development : life stories, middle managers and the leader-follower paradox : a thesis presented in partial fulfilment of the requirements for the postgraduate degree of Master of Advanced Leadership Practice at Massey University, Albany, New Zealand - Knowsley, Mathew David (Massey University, 2017)
There is a small amount of emergent leadership literature recommending people incorporate a narrative based approach into their leader development. This approach involves the identification and reflection on experiences and events from ones’ life so a story can be told about who they are as a leader (life stories). To date, life stories research has yet to account for the fact leaders must also follow. Middle managers embody this paradox. This study was an investigation into the potential for life stories to contribute to middle managers’ leader development. This study also looked at how life stories might contribute to middle managers understanding of themselves as followers and how they might use life stories in negotiating the leader-follower paradox. The overall aim was to make a further contribution to understanding the potential for life stories in leader development. A case study of five Auckland New Zealand based middle managers was conducted. Life history interviews were thematically analysed using life stories as a sensitizing concept. Participants demonstrated little to no previous knowledge, skill or experience in life stories as a development process. They told stories as leaders that generally implied existing life stories self-development themes but they did not explicitly identify them. They told stories as followers that were somewhat at odds with general opinions they held on following. There was little correlation with existing life stories self-development themes. Overall, Participants’ life stories base intrapersonal leader and follower self-narratives had potential to be coherent, but were instinctive and under-developed. Participants’ ability to draw on life stories to identify, discuss and negotiate the leader-follower paradox matched their existing integration of life stories and intrapersonal leader-follower identities. Overall, participants had potential to produce a coherent and integrated leader-follower narrative, but this potential was under-developed. More research is required. A narrative based framework for further leader-follower life stories development processes is offered as a starting point.
Keywords: 350707 Leadership